Literature Review: Analysis of The Presentation of Humanity Conditions: A Case Study of Inherent Houses in Indonesia - Natasya Putri Lika; Sri Wahdina Tanjung; Abdurrozzaq Hasibuan (RADINKA JAYA UTAMA PUBLISHER, 2024)
This study aims to analyze fire emergency preparedness in Indonesian hospitals through a systematic review of previous studies. Using a systematic literature review method, this study identified and synthesized key findings from related studies. The results showed that fire emergency preparedness in hospitals in Indonesia still needs improvement, especially in terms of emergency response systems, human resource capacity, availability of facilities and infrastructure, and coordination with related parties. Efforts to improve preparedness need to be carried out comprehensively, involving collaboration between hospitals, government, fire department and the community.